Maternal exposure to di-n-butyl phthalate (DBP) promotes epithelial-mesenchymal transition via regulation of autophagy in uroepithelial cell. (1st August 2018) - Zhao, Sheng; Li, Deng; Bei, Xiao-Yu; Zhu, Yi-Ping; Sun, Wen-Lan; Shen, Cheng; Wood, Kristofer; Han, Bang-Min; Jiang, Jun-Tao
Abstract: Maternal exposure to di-n-butyl phthalate (DBP) induces hypospadias, but the underlying mechanisms remain elusive. Here we hypothesize that aberrant activation of autophagy and epithelial-mesenchymal transition (EMT) are the leading cause of DBP-related hypospadias. Pregnant rats received DBP orally at a dose of 750 mg/kg/day during gestational days 14–18. In DBP-induced hypospadiac male offspring, immunohistochemistry (IHC) staining and Western blot showed increased expression of autophagy and EMT markers in genital tubercle (GT) tissue compared to the control. In addition, lower testosterone levels and androgen receptor (AR) expression in GT tissue were detected. In vitro studies revealed that impaired AR signaling was involved in DBP-induced autophagy and autophagy activation furthermore promoted EMT in urethral epithelial cells. DBP combined with chloroquine, an autophagy inhibitor, reduced the expression of EMT markers compared with DBP treatment alone, while DBP combined with the autophagy inducer rapamycin elevated the expression of EMT markers. The autophagy-lysosomal pathway inhibitor CQ but not proteasome inhibitor MG-132 rescued the decrease of E-cadherin after DBP treatment, which indicated autophagy-induced E-cadherin degradation contributes to DBP-related EMT. Taken together, our findings show that prenatal exposure to DBP induces abnormal autophagy and EMT that may play important roles in hypospadias development.